Perspective of Caesarean section delivery and its health risks on children among Indonesian pediatricians - Ray Wagiu Basrowi; Tonny Sundjaya; Nova Lidia Sitorus; Bertri Maulidya Masita (Indonesian Nutrition Association, 2020)
An increasing trend of C-section delivery In Indonesia was found from 2% in 1986 to 16% in 2012. This delivery method was introduced to save women and their newborn baby’s life. On the other side, it can increase short and long-term health risks for children. This study aims to assess and give an overview of the perspective on pediatrician as medical specialist in managing children of the C-section delivery history. A survey was conducted on 89 Indonesian Pediatricians using an online questionnaire. It was found that most pediatrician chose combination partial hydrolyze milk combined with synbiotic (a combination of prebiotic and probiotic) combination as nutrition intervention to decrease the allergy risk on children with C-section delivery mode, and there is a need to emphasize information about short and long-term health effects of C-section, especially in causing gut dysbiosis and its mechanism, information on non-medical causes of gut dysbiosis to increase awareness of recommending right symbiotic to decrease allergy risk in children with C-section history.